Customers Co-Creation Intention: The Mediating Role Of Customer Brand Engagement On Social Media In Fashion Retail - Abdelaziz, Kesmat Mohamed Elsayed (2022)
Social media has become an important channel for marketing activities shaping customer brand engagement (CBE) and interactions. Empowered by the rise of social media, customers are no longer a ‘passive audience’ but ‘active co-producers’ who engage in behaviours that strengthen their relationship with the product or brand, such as value co-creation for innovation, particularly in the fashion retail context. Customer value co-creation is critical for marketing success and innovation, especially for fashion Micro and SMEs (MSMEs) facing rigid competition with larger firms. However, many firm-initiated co-creation activities face difficulties in attracting and engaging promising customers. Therefore, research is needed to investigate the factors influencing CBE for value co-creation intention since previous research in this area is limited. Additionally, social media allowed the emergence of influencer marketing and endorsements which significantly shape customers’ behaviors and intentions including value co-creation intention. Based on the social cognitive theory, this thesis aims to develop a research model to understand the factors influencing customers’ value cocreation intention behavior from the perspective of customer brand engagement. Moreover, social effect theory was integrated to investigate the effect of influencer marketing on customers’ value co-creation intention.